Reduced allergenicity of tomato fruits harvested from Lyc e 1-silenced transgenic tomato plants - Sonnewald, Uwe; et al. (Journal of Allergy and Clinical Immunology, 2006)
Clinical implications: Our findings demonstrate the feasibility of creating low-allergenic food by using RNAL This concept constitutes a novel approach to allergen avoidance.
Keywords: Lyc e 1; RNA interference; tomato allergy; allergen avoidance